Budaya Hukum Penyelesaian Perkara Berbasis Restorative Justice di Desa Sintung, Lombok Tengah - Muhammad Rosikhu; Suheflihusnaini Ashady; Nakzim Khalid Siddiq (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2023)
In an effort to resolve cases, when the victims are women as part of a marginal group, inequality often occurs. Men who hold authority to resolve cases often take sides and incriminate their victims so that the values of legal certainty, justice and expediency are difficult to achieve even though there is peace as a result of the settlement of the case. Besides women, small communities or marginalized groups, people with disabilities are also included in marginal groups. Access to certainty, justice and the benefit of the law is a necessity that this marginal group must obtain. The law must not be dominated by certain groups who are close to certain power, capital, or social status. This problem occurs because part of the inheritance has not been handed over to the rightful party, for this problem then the Village Sangkep Hall carries out a restorative justice process. Finally, an agreement is reached in which one the aggrieved party gets his share and the party who controls the object of the dispute submits it knowingly and voluntarily. The problem ended with each party making a statement that contained a willingness to end the case and not sue each other in the future. Restorative justice has not been comprehensively regulated in various laws and regulations in Indonesia, the term restorative justice is only regulated in the Act. Number 11 of 2012 concerning the Juvenile Criminal Justice System. Sintung Village, in the process of resolving cases, has fulfilled the main principles of restorative justice. This process has succeeded in maintaining order and security in the Sintung Village environment, in addition, the community also supports the existence of the Village Sangkep Hall.